Modalities to collaborate in the social construction of conceptual maps : a comparison between individual and collective productions - Roselli, Néstor Daniel (2017)
Fil: Roselli, Néstor. Pontificia Universidad Católica Argentina; Centro de Investigaciones en Psicología y Psicopedagogía; Argentina